The Role of Experience in the Visual and Non-Visual Prey Recognition of Fire Salamander Populations from Caves and Streams - Hayes Hoover; Raoul Manenti; Andrea Melotto (Diversity, 2024)
The study of foraging behaviour is crucial for understanding several ecological and adaptive processes, as well as for developing conservation measures. While extensive research has been completed on birds and mammals, few studies have been conducted on the learning capabilities of amphibians, particularly those pertaining to foraging behaviour. Amphibians may detect potential prey through distinct sensory systems including visual detection, chemoreception, and mechanoreception. In this study, we tested whether fire salamander larvae shift their prey recognition depending on the prey stimulus typology. We performed behavioural assays to better understand the roles of visual and chemical cues in prey recognition and how a continuative visual stimulus may change behavioural patterns. For this assessment, larvae from different habitats (cave and stream) were reared under laboratory conditions and fed while exposed to accompanying sensory stimuli. Their responses to visual and olfactory cues were measured before and after rearing. Both visual and chemical cues significantly affected the time of approach to the stimulus. The period of rearing significantly interacted with the time of approach for both cues. After rearing, when visual cues occurred, the time of approach was much lower than before rearing. These findings provide a basis for further studies on the role of plasticity in the predator–prey interactions of fire salamander larvae.